FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN SAYURAN ORGANIK DI KOTA PALU - Paradiba, Dela; Mappatoba, Marhawati; Lamusa, Arifuddin (AGROTEKBIS, 2017)
This study aimed to determine the factors that affect the demand of organic vegetables in the city of Palu. The research conducted in the city of Palu in December 2016 to January 2017. The analysis tool used is multiple linear regression, using the F test (simultaneous) and t test (Partial). The results showed that the factors that affect the demand of organic vegetables in the city of Palu simultaneously are all the income variable (X1), the price of organic vegetables (X2) and the price of substitution goods (X3) together effect significantly on the dependent variable ( Y). As partially, the revenue (X1) tcalt. (10,391) > t table (1,699) and the price of organic vegetables (X2) tcalt. (2,477) > t table (1,699), it means that the variable income and the price of organic vegetables have a value of tcalt. > t table showing the two variables significantly influence the dependent variable (Y), while the price of the substitution (X3) tcalt. (0,728) < t table (1,699), it means thet the variable price of the substitution good has the value tcalt. < t table that shows does not significantly influence on the dependent variable (Y). Keywords: Demand, multiple linear regression, organic vegetable.